THE PROBLEMATICS OF IMPLEMENTING RESTORATIVE JUSTICE AT THE INVESTIGATION STAGE IN INDONESIA - Riffan Abvaliandro (Fakultas Hukum Universitas Komputer Indonesia, 2025)
Restorative justice represents a paradigm shift in criminal law philosophy, moving from a purely retributive approach toward a more rehabilitative and reconciliatory model. In the Indonesian legal landscape, the implementation of restorative justice particularly at the investigation stage has attracted considerable scholarly attention and practical debate. While regulatory frameworks such as the Regulation of the Chief of the Indonesian National Police (Peraturan Kapolri) Number 8 of 2021 and the Regulation of the Attorney General Number 15 of 2020 provide formal foundations, significant problematics persist in their practical application. This article examines the conceptual underpinnings of restorative justice, its normative basis within the Indonesian criminal justice system, and the multidimensional challenges encountered during its implementation at the investigative stage. Through a normative juridical method with a statutory and conceptual approach, this study identifies four central problematics: the absence of a unified national legal framework, the discretionary power of investigators and its potential for abuse, the lack of standardized mechanisms for victim participation and protection, and the tension between restorative principles and the formal due process guarantees under Indonesian criminal procedure law. The study argues that systematic legislative reform, comprehensive capacity building for law enforcement officers, and institutional accountability mechanisms are prerequisites for effective and just restorative justice implementation in Indonesia. Keadilan restoratif merupakan pergeseran paradigma dalam filsafat hukum pidana, dari pendekatan yang semata-mata bersifat retributif menuju model yang lebih rehabilitatif dan rekonsiliatoris. Dalam lanskap hukum Indonesia, implementasi keadilan restorative khususnya pada tahap penyidikan telah menarik perhatian akademis dan perdebatan praktis yang cukup signifikan. Meskipun kerangka regulasi seperti Peraturan Kapolri Nomor 8 Tahun 2021 dan Peraturan Jaksa Agung Nomor 15 Tahun 2020 telah memberikan landasan formal, berbagai problematika masih terjadi dalam penerapan praktisnya. Artikel ini mengkaji landasan konseptual keadilan restoratif, dasar normatifnya dalam sistem peradilan pidana Indonesia, serta tantangan multidimensional yang dihadapi selama implementasinya pada tahap penyidikan. Melalui metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual, studi ini mengidentifikasi empat problematika utama: ketiadaan kerangka hukum nasional yang terpadu, kekuasaan diskresi penyidik dan potensi penyalahgunaannya, ketidaktersediaan mekanisme standar bagi partisipasi dan perlindungan korban, serta ketegangan antara prinsip restoratif dan jaminan due process formal berdasarkan hukum acara pidana Indonesia. Studi ini berargumen bahwa reformasi legislatif yang sistematis, peningkatan kapasitas komprehensif bagi aparat penegak hukum, serta mekanisme akuntabilitas kelembagaan merupakan prasyarat bagi implementasi keadilan restoratif yang efektif dan adil di Indonesia.